Technology-Enabled Business Model Innovation Through Agricultural Drone Adoption in Spraying and Fertilization Services: A Case Study of a Plantation Company - Raezan Fadilla Noor; Wawan Dhewanto (Cv. Syntax Corporation Indonesia, 2026)
The adoption of digital technologies in agricultural service operations is often assessed through operational or technical performance outcomes, while their implications for business model innovation remain underexplored. This study examines how agricultural drone adoption enables business model innovation in spraying and fertilization services, focusing on managerial interpretation and organizational reconfiguration rather than performance measurement. Using a qualitative single-case study approach, data were collected through semi-structured interviews with managerial and operational personnel, supported by organizational documents. The analysis is guided by the Business Model Navigator framework, examining changes across the Who–What–How–Why dimensions and interpreting business model innovation as an incremental process. The findings indicate that agricultural drone adoption initially emerged as a response to operational challenges such as labor scarcity, execution speed, and monitoring limitations. Over time, continued use of drone technology prompted managerial reframing, leading to gradual adjustments in value creation, service transparency, and operational control. Rather than resulting in radical transformation, drone adoption supported incremental business model reconfiguration by layering technology-enabled coordination and data utilization onto existing service structures. The study highlights that the strategic value of agricultural drones lies not only in operational support, but also in their capacity to reshape managerial decision-making and service logic through business model alignment. These findings contribute to the business model innovation literature by demonstrating how digital technologies can function as strategic triggers for incremental business model change in service-based agricultural contexts.